The world without you ebook A novel. - Henkin, Joshua (2012)
***National Jewish Book Awards 2012, Finalist***       JJ Greenberg Memorial Award for Fiction From the author of the New York Times Notable Book Matrimony ["Beautiful . . . Brilliant."—Michael Cunningham], a moving, mesmerizing new novel about love, loss, and the aftermath of a family tragedy. It’s July 4, 2005, and the Frankel family is descending upon their beloved summer home in the Berkshires. But this is no ordinary holiday. The family has gathered to memorialize Leo, the youngest of the four siblings, an intrepid journalist and adventurer who was killed on that day in 2004, while on assignment in Iraq. The parents, Marilyn and David, are adrift in grief. Their forty-year marriage is falling apart. Clarissa, the eldest sibling and a former cello prodigy, has settled into an ambivalent domesticity and is struggling at age thirty-nine to become pregnant. Lily, a fiery-tempered lawyer and the family contrarian, is angry at everyone. And Noelle, whose teenage years were shadowed by promiscuity and school expulsions, has moved to Jerusalem and become a born-again Orthodox Jew. The last person to see Leo alive, Noelle has flown back for the memorial with her husband and four children, but she feels entirely out of place. And Thisbe —Leo’s widow and mother of their three-year-old son—has come from California bearing her own secret. Set against the backdrop of Independence Day and the Iraq War, The World Without You is a novel about sibling rivalries and marital feuds, about volatile women and silent men, and, ultimately, about the true meaning of family.